The Influence of Particle Size on the Efficiency of Ni Mining Slag as a Fertilizer - de Melo, Carlos Vinícius Cavalini Batista [UNESP]; Moretti, Luiz Gustavo [UNESP]; Bossolani, Joao William [UNESP]; Momesso, Letusa [UNESP]; de Campos, Murilo [UNESP]; Portugal, Jose Roberto [UNESP]; Calonego, Juliano Carlos [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Springer Nature, 2022)
Thermomagnesium (TM) is a potential alternative fertilizer, but information about its physical characteristics, especially the most suitable granulometric fraction to increase agronomic efficiency, is lacking. The objective of this study was to evaluate the relationship between TM particle size and agronomic efficiency. The study was carried out in a crop rotation system during the 2018/2019, 2019, and 2019/2020 seasons for soybean, maize, and soybean, respectively. The effects of two different particle sizes of TM, i.e., 20 and 100 mesh, on soil chemical attributes, leaf nutritional content, leaf sugar concentration, leaf pigments, 100 grain weight, and grain yield, were evaluated in eight replications. Positive responses of chlorophyll a, carotenoids, and total chlorophyll to both particle sizes of TM were observed. TM application, especially 100 mesh, increased the leaf concentrations of reducing sugars and sucrose in the first soybean crop and maize but not in the second soybean crop. TM application reduced leaf starch concentrations regardless of crop or particle size. Increases in 100 grain weight were observed in soybean under 100-mesh TM application and in maize under both particle sizes. Application of 100-mesh TM increased the grain yield of the first soybean crop and maize, whereas no impact of TM application on the grain yield of the second soybean crop was observed. Although additional studies of particle size are needed, TM can be considered a suitable source of magnesium and silicon for crops, especially when ground to a particle size of 100 mesh.
Keywords: Byproduct; Crop nutrition; Environmental safety; Soil remineralizer